Interdisciplinary Take on Augmented Reality - Bździuch, Sławomir (Journal of Education, Technology and Computer Science, 2022)
This publication attempts to show the interdisciplinary nature of augmented reality. With the development of technology and the widespread use of smartphones, there has been a great development of AR technology. This technology, due to its universal nature, is used in various spheres of everyday life. Discussing the interdisciplinary nature of this technology within the scope of this publication, the author focused on the possibilities of its use in education, medicine and marketing. By pointing out practical examples of the use of AR, the author will show how this technology is entering everyday life. The choice of the areas indicated is intended to show that AR technology will be used by the majority of society in the future. This is due to the fact that this technology has great prospects for development with particular emphasis on the areas mentioned.